(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2023)
Municipalized Education needs to be conceived in an inclusive way where the student is accepted as he is, respecting his human condition, his cultural diversity, and with the deserved attention to his geographical spaces from the local, the regional and vice versa; to go to the reunion of the communities that claim to be recognized with their cultural repertoire. We must learn to face education from a change of innovative thinking, overcoming the outdated antinomies and divisions of topois, theory and practice, hard sciences, soft sciences; knowledge, knowledge; among other. The complex objective of this inquiry is to support complex strategies in educability - municipalized university education - complex social imaginaries. It is a complex, decolonial inquiry that tends to go beyond traditional philosophy. In this triad, complex strategies are shown in the light of planetary decoloniality, in its theory and practice. Taking into consideration their reconstructions in the ecology of action. It must be clear that from the complexity all strategy leads us to one or other actions to follow for its realization, a complex strategy requires seven (7) conditions that make it complex and recursive in its practicality; These are: system, circularity, dialogic, complex causality, interactions, polyrelational circles, and reconnection. For this we attend, with the transmethod, rhizomatic deconstruction, because it allows us to disarm rigid structures to search, explore and investigate and at the same time break with the old scheme of oppressive and reductionist thought in order to feel free and without ties to go in search of new expectations to consolidate the educational process from the municipalization.